ANALISA PENGUNGKAPAN SUSTANABILITY REPORTING PT. PETROKIMIA GRESIK BERDASARKAN SUSTAINABILITY DEVELOPMENT GOAL (Sustainable Development Goals (SDGs) ) TAHUN 2021 - Tiara Kusuma Dewi (ARTHA SATYA DHARMA, 2023)
This research to know to reveal the contribution of achieving sustainability Development Goals to the sustainability performance of PT. Petrokimia Gresik in 2022. PT. Petrokimia Gresik is one of the companies that received a Platinum rating from the Asian Sustainability Reporting Rating (ASRRAT). The purpose of this research is to analyze the disclosure of Sustainable Development Goals as reflected in PT's Sustainability Report. Petrokimia Gresik in 2022 based on GRI Standards in 2022. This type of research is qualitative research. The research method used is the content analysis method. The data collection technique used is documentation, namely collecting relevant data and information sourced from literature studies and internet searches in order to obtain information that is useful for conducting research. The conclusions obtained in this research are based on the results of the research showing that based on the ranking of the Predicate for Suistainability Reporting Disclosures for the 2022 period it can be categorized as informative with an average data processing value of 70%. In this report, the disclosures reported have been categorized as accurate. It is hoped that PT. Petrokimia Gresik in 2022, maintaining the quality of sustainability reports.